(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The print media has proven to be a powerful communication medium on issues such as climate change, depletion of energy resources, use of renewable and conventional energy sources and their impact on the quality of life of society, biodiversity and ecosystems, serving as a means of raising awareness. Additionally, the energy consumption of print media facilities contributes to these changes, as a result of greenhouse gas emissions from the consumption of electricity in its newsroom processes and in the printing of copies, in the case of paper newspapers. This paper shows the results obtained from the analysis of the electric energy consumption of a newspaper printing company obtained from an energy audit. The results show that with measures on the air conditioning equipment systems, benefits are reflected as a better redistribution of the energy matrix and a reduction in energy consumption, which is reflected in the estimated energy efficiency indexes based on the number of printed copies, employees and construction area.